Respuesta :
i dont get it at all ithink you need to take this part out -$1.00 per hotdog;$0.50 per soda -$1.25 per hotdog;$0.75 per soda -$1.50 per hotdog;$0.75 per soda -$2.00 per hotdog; $1.00 per soda
Answer:
[tex]\$1.25[/tex] per hot dog and [tex]\$0.75[/tex] per soda
Step-by-step explanation:
Let
x------> the charge per hot dog
y-----> the charge per soda
we know that
[tex]2x+2y=4[/tex] ------> equation A
[tex]3x+y=4.50[/tex] ------> equation B
Multiply by [tex]-2[/tex] equation B
[tex]-2(3x+y)=-2*4.50[/tex]
[tex]-6x-2y=-9[/tex] ------> equation C
Adds equation A and equation C
[tex]2x+2y=4\\-6x-2y=-9\\---------\\ 2x-6x=4-9\\-4x=-5\\x= \$1.25[/tex]
Find the value of y
[tex]3x+y=4.50[/tex]
[tex]3(1.25)+y=4.50[/tex]
[tex]y=4.50-3.75=\$0.75[/tex]
therefore
[tex]\$1.25[/tex] per hot dog and [tex]\$0.75[/tex] per soda